PHYSICOCHEMICAL AND SENSORY CHARACTERISTICS OF CRISPY ALMOND PRODUCTS WITH PUMPKIN FLOUR SUBSTITUTION - Fadjar Kurnia Hartati; Pamela Felita Tjendra; Yuyun Yuniati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Pumpkin flour has the potential to be used as a substitute for wheat flour due to its high fiber and micronutrient content. This study aims to analyze the effect of pumpkin flour substitution on the physicochemical and sensory characteristics of almond crispy and to determine the best formulation. The study used a single-factor Completely Randomized Design with five substitution levels (0%, 30%, 40%, 50%, and 70%) and three replications. The parameters observed included moisture content, ash content, fiber content, and organoleptic tests (color, taste, aroma, and texture). Data were analyzed using ANOVA and the Kruskal–Wallis test . The results showed that pumpkin flour substitution significantly affected fiber content and sensory attributes, but did not significantly affect moisture and ash content. Increasing the proportion of pumpkin flour increased fiber content but tended to decrease panelists' preference level. Based on the effectiveness test, the formulation with 70% pumpkin flour substitution produced the best combination of chemical and sensory qualities, so it has the potential to be developed as a high-fiber functional food product.